The Effect of Brand Image and Product Quality on Purchase Decision of Starbucks Coffee in Malang City - Cita Della Dwi Riyanika; Ratih Juliati; Kenny Roz (Jamanika (Jurnal Manajemen Bisnis dan Kewirausahaan), 2022)
The purpose of this study was to determine and analyze the effect of brand image and product quality on Starbucks Coffee purchasing decisions in Malang City. The population in this study were all consumers who bought Starbucks Coffee in Malang, with a sample of 120 respondents who were taken using the Nonprobability Sampling technique with the Snowball Sampling method. The characteristics of respondents are respondents who bought Starbucks Coffee for the first time by delivery orders through the Grab, Gojek, and Shopee Food applications and respondents who had bought other coffee brands. The time of the research was February 2 – March 5, 2022, distributing online questionnaires. The data analysis technique was carried out using multiple linear regression analysis, t-test, and dominant test. The results of this study conclude that brand image and product quality have a positive and significant effect on purchasing decisions. Due to a large number of competitors, brand image has a dominant effect on purchasing decisions, which is contrary to the hypothesis